Advanced Persistent Security : A Cyberwarfare Approach to Implementing Adaptive Enterprise Protection, Detection, and Reaction Strategies /: A Cyberwarfare Approach to Implementing Adaptive Enterprise Protection, Detection, and Reaction Strategies. (2016) - Winkler, Ira; Treu Gomes, Araceli
No abstract available